Dexmedetomidine alleviates lung ischemia-reperfusion injury by inhibiting cuproptosis: an in vivo study - Liu, Hanqun; Wang, Zicheng; Qiu, Tong; Du, Wenxing; Wu, Zhe; Chen, Sheng; Jiao, Wenjie (Frontiers in Pharmacology, 2025)
Lung ischemia-reperfusion (I/R) injury represents an inevitable complication in lung transplantation, characterized by the excessive production of oxygen free radicals and toxic substances. Dexmedetomidine (DEX), a widely used anesthetic agent, has been shown to significantly elevate glutathione (GSH) levels, thereby conferring protection against copper influx. This study investigates the protective mechanisms of DEX in lung I/R injury, with a particular focus on cuproptosis. Utilizing a rat I/R model established by clamping the left hilum of lung for 90 min followed by 120 min of reperfusion, we examined the effects of DEX on lung injury scores, GSH content, and the expression of key proteins involved in cuproptosis. In conclusion, cuproptosis is implicated in pulmonary I/R injury, and the protective effect of DEX against lung I/R injury is partly mediated by inhibition of cuproptosis.